BEBAN KOGNITIF DAN MATHEMATICAL RESILIENCE MAHASISWA PADA PEMBELAJARAN MATEMATIKA DI PERGURUAN TINGGI : STUDI DESKRIPTIF-KORELASIONAL: Beban Kognitif Dan Mathematical Resilience Mahasiswa Pada Pembelajaran Matematika Di Perguruan Tinggi : Studi Deskriptif-Korelasional - Lapele, Dina Amalya; Mastuti, Ajeng Gelora; A'yun, Qurrota (Journal of Mathematics Learning Innovation, 2026)
This study aims to describe the condition of cognitive load and mathematical resilience of students in mathematics learning and their relationship. This study uses a quantitative approach with a descriptive-correlational design. The population in this study were students of the Mathematics Education Study Program at the A. M. Sangadji State Islamic University, Ambon. The sample consisted of 33 students taken using a convenience sampling technique. Data were collected through a survey distributed online via Google Forms. The instruments used were a cognitive load questionnaire and a mathematical resilience questionnaire. Data were analyzed using descriptive statistics (mean, standard deviation, mode, minimum, maximum) and the Spearman correlation test. The results showed that the condition of students' cognitive load was quite low, while their mathematical resilience was very high. Cognitive load and mathematical resilience have an indirect relationship and are classified as very weak. The lower the cognitive load, the higher the mathematical resilience, and vice versa. The findings of this study can be implied in designing mathematics learning that minimizes cognitive load to maximize mathematical resilience.